Exploring the Transformative Potential of Cloud Computing in Distance Education: Challenges, Opportunities, and Best Practices - Carissa Maharani; Indah Nutela (Institute of Computer Science (IOCS), 2024)
This research explores the use of cloud computing technology in distance education, investigating its transformative potential, challenges, and best practices. Through a mixed-methods approach combining quantitative surveys and qualitative interviews, the study examines the impact of cloud-based solutions on educational institutions, educators, and students. Findings reveal that cloud computing enhances accessibility, scalability, and educational outcomes by democratizing access to learning resources, facilitating personalized instruction, and streamlining administrative processes. However, challenges such as data security, privacy issues, and technical support require proactive strategies and best practices to mitigate risks and ensure the reliability of cloud-based systems. The research highlights the critical role of collaboration between educational institutions, industry partners, and policymakers in driving forward the adoption of cloud computing in education and shaping a brighter future for distance learning.